Feminizmas teatre: tarp dialogo ir kraštutinės ideologijos - Bartoševičiūtė, Gabrielė Uršulė (Institutional Repository of Lithuanian Academy of Music and Theatre, 2020)
SUMMARY This paper investigates the relations of the social, political, economic and societal movement feminism insofar as it affects theatre within the statistics of the field, methods of creative process and its expression. The statistics released in 2019 indicate that Lithuania has not made any progress in the field of gender equality since 2005, and therefore it is crucial to examine how systematic and internalized sexism correlates with artistic and social – societal processes. This paper is divided into four parts and acts as a full-fledged study of feminism in theatre using diverse perspectives. This research uses the premise of women as “Other” proposed by Simone de Beauvoir: contemplating on woman, which was created by and for Man, it aims to give feminism a time and location frame, describe its waves and find its manifestation within theatre in general terms. In the second part, the author offers an innovative approach to the organisation of creative process by including feminism as a creative strategy. This strategy aims not only for the world portrayed on stage, but also for rehearsal processes and structuration of work, contextualisation, and usage of the tools proposed by intersectional feminism. In the third part, potentially adverse effects of feminism are discussed i.e. censorship and euphemizing of rhetoric and phenomena in theatrical discourses. The last part, studies the example of the show “Requiem for a Woman” (dir. Uršulė Bartoševičiūtė, produced by Lithuanian State Youth Theatre, Lithuanian Music and Theatre Academy and Iceland University of the Arts, premiered at culture bar KABLYS+CULTURE on 19 and 20 of August 2020). The creative process where feminism was employed as a creative strategy and stimulated a healthy dialogue amongst all members of the creative team is scrutinized in this part. This research aspires to create a supplemented theatrical theory and practice that is capable of encompassing and systematizing the need of intersectional feminism in theatre.